Emotional intelligence and success in initial vocational education and training: A study among healthcare assistants and social care workers - Laure Tremonte-Freydefont; Matilde Wenger; Marina Fiori (International Journal for Research in Vocational Education and Training (IJRVET), 2024)
Context: Research on emotional intelligence (EI) shows this concept's decades-long positive influence on well-being, self-efficacy, employability, and academic and professional achievement. Indeed, several studies have demonstrated that students with high EI have better grades and quality of life, as well as are more employable than students with low EI. By considering the two conceptualizations of EI as either an ability or personality trait, the present study investigates EI's influence on training achievement in initial vocational education and training (IVET). We posited that the two types of EI positively influence training achievement in a complementary way: Ability EI relates to achievement in theoretical training, while trait EI relates to achievement in practical training. Furthermore, these links are mediated by apprentices' engagement at school and in learning. Method: To test our hypotheses, 92 dual IVET health and social care apprentices in their last year of vocational school completed an online survey composed of validated scales measuring EI as an ability, EI as a personality trait, personality traits, and school engagement. The apprentices' grades were also obtained with their permission. Results: The findings confirmed our hypotheses and reflected EI's positive influence on training achievement. We observed that participants with high EI (as an ability and personality trait) obtained better grades than participants with lower EI. Moreover, our results showed that ability EI has a direct influence on achievement in theoretical health and social care training, while the link between trait EI and practical training is indirect and mediated by engagement in learning. Conclusion: The present study confirms EI's positive influence on school achievement in the VET context and further corroborates the important role that EI can play in dual IVET apprentices' achievement, particularly in the health and social sectors. This original study contributes to research on the VET system by placing EI among the skills necessary to ensure professional success.
Keywords: 330; Apprenticeship; Emotional Intelligence; Health and Social Care Sectors; Initial Vocational Education and Training; Training Achievement; VET